Beyond the welfare state : postwar social settlement and public pension policy in Canada and Australia - Karimi, Sirvan, 1966- (Studies in comparative political economy and public policy, 2017)
"Neoliberal calls for welfare state reforms, especially cuts to public pensions, are a contentious issue for employees, employers, and national governments across the western world. But what are the underlying factors that have shaped the response to these pressures in Canada and Australia? In Beyond the Welfare State, Sirvan Karimi utilizes a synthesis of Marxian class analysis and the power resources model to provide an analytical foundation for the divergent pattern of public pension systems in Canada and Australia. Karimi reveals that the postwar social contract in Australia was market-based and more conducive to the privatization of retirement income. In Canada, the social contract emphasized income redistribution that resulted in strengthening the link between the state and the citizen. By shedding light on the impact of national settings on public pension systems, Beyond the Welfare State introduces new conceptual tools to aid our understanding of the welfare state at a time when it is increasingly under threat."--